2010
DOI: 10.1111/j.1349-7006.2010.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor enhances the migration of gastric cancer through downregulation of E‐cadherin via the NF‐κB pathway

Abstract: Local invasion and distant metastasis are difficult problems for surgical intervention and treatment in gastric cancer. Connective tissue growth factor (CTGF/CCN2) was considered to have an important role in this process. In this study, we demonstrated that expression of CTGF was significantly upregulated in clinical tissue samples of gastric carcinoma (GC) samples. Forced expression of CTGF in AGS GC cells promoted their migration in culture and significantly increased tumor metastasis in nude mice, whereas R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…CTGF is a cysteine-rich protein that belongs to the CCN family and is reported to interact with several growth factor signaling pathways, including transforming growth factor-b, bone morphogenetic protein, and Wnt (23)(24)(25). Mao et al reported that CTGF can stimulate nuclear factor-kB signaling and thus contribute to the metastasis of GC (26). There is also a report that CTGF is associated with the radiorecovery response of the early growth plate 2 weeks after irradiation (17).…”
Section: Introductionmentioning
confidence: 94%
“…CTGF is a cysteine-rich protein that belongs to the CCN family and is reported to interact with several growth factor signaling pathways, including transforming growth factor-b, bone morphogenetic protein, and Wnt (23)(24)(25). Mao et al reported that CTGF can stimulate nuclear factor-kB signaling and thus contribute to the metastasis of GC (26). There is also a report that CTGF is associated with the radiorecovery response of the early growth plate 2 weeks after irradiation (17).…”
Section: Introductionmentioning
confidence: 94%
“…In chondrosarcoma cells, CCN2/CTGF enhances cell migration by matrix metalloproteinase-13 upregulation through integrin α5β3 [55] and in gastric cancer through downregulation of E-cadherin by NF-κB pathway [56]. Curiously, neutralizing anti-CCN2/CTGF antibody attenuated metastasis pancreatic cancer [57]. In cancer and in metastasis, the role of CCN2/CTGF seems to be the same.…”
Section: Ccn2/ctgf Historical Profilementioning
confidence: 99%
“…NF-κB activation has been frequently observed in both gastric cancer cells [13-16] and tumor-infiltrating lymphocytes [17]. In addition, down-regulation of NF-κB has been shown to suppress cell migration and invasion in gastric cancer cells in vitro [16,18]. Thus, modulation of the NF-κB pathway might be a promising therapeutic target for gastric cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%